PENGARUH PRESTASI BELAJAR, EFIKASI DIRI DAN LINGKUNGAN TEMAN SEBAYA TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI SISWA KELAS XII SMA NEGERI 1 HAMPARAN PERAK - Aisyah Amini Siregar; Pasca Dwi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of Academic Achievement, Self-Efficacy, and Peer Environment on the interest in continuing education to higher education among 12th-grade students at SMA Negeri 1 Hamparan Perak. This type of research is quantitative. The study has a population of 152 students. The technique used in this study is Proportional Random Sampling, due to the population size of 152 students. The data collection technique used is through filling out questionnaires. The data analysis technique used is multiple linear regression with hypothesis testing, namely Partial Test (t-Test), Simultaneous Test (F-Test), and the coefficient of Determination. Based on the data analysis, the resukts indicate that Academic Achievement, Self-Efficay, dan Peer Environment have a positive and significant influence on students’ interest in pursing higher education among Grade XII students of SMA Negeri 1 Hamparan Perak.